Explorations in Early Southeast Asian History The Origins of Southeast Asian Statecraft - Hall, Kenneth R.; Whitmore, John K. (Michigan Papers On South And Southeast Asia, 2020)
While following the probes of foreign individuals into various obscure parts of Southeast Asia over the centuries is a diverting and entertaining pastime, the purpose of this volume is to investigate this past with the mind, to question and postulate upon the historical patterns that have developed from earlier study of the area, and to bring concepts from other areas and disciplines to bear on the existing information. The product of this effort, as it is encompassed in this volume, is not an attempt at the definitive study of any of the topics. It is rather a series of speculations on the directions feasible for the further study of the Southeast Asian past. As such, the answers proposed in these essays are really questions. Are the ideas presented here true within the specific historical contexts for which they have been developed? If so, can we use these ideas, or variations of them, to interpret the history of other parts of Southeast Asia? If not, what other ideas may be brought to bear on these situations in order to understand them? The ultimate aim of this volume is thus a challenge to the profession at large not only to criticize what we have done, but also to go beyond our postulations and create new ones. [xi]